Leucine periodicity of U2 small nuclear ribonucleoprotein particle (snRNP) A' protein is implicated in snRNP assembly via protein-protein interactions. - Fresco, L D (1991)
Recombinant A' protein could be reconstituted into U2 small nuclear ribonucleoprotein particles (snRNPs) upon addition to HeLa cell extracts as determined by coimmunoprecipitation and particle density; however, direct binding to U2 RNA could not be demonstrated except in the presence of the U2 snRNP B" protein. Mutational analysis indicated that a central core region of A' was required for particle reconstitution. This region consists of five tandem repeats of approximately 24 amino acids each that exhibit a periodicity of leucine and asparagine residues that is distinct from the leucine zipper. Similar leucine-rich (Leu-Leu motif) repeats are characteristic of a diverse array of soluble and membrane-associated proteins from yeasts to humans but have not been reported previously to reside in nuclear proteins. Several of these proteins, including Toll, chaoptin, RNase/angiogenin inhibitors, lutropin-choriogonadotropin receptor, carboxypeptidase N, adenylyl cyclase, CD14, and human immunodeficiency virus type 1 Rev, may be involved in protein-protein interactions. Our findings suggest that in cell extracts the Leu-Leu motif of A' is required for reconstitution with U2 snRNPs and perhaps with other components involved in splicing through protein-protein interactions.